Optimization of Process Parameters for A Wind Turbine in A Ducting System Through The Taguchi-Pareto-DEMATEL Method - Oke, Sunday Ayoola; Abayomi, Oluwatayo Johnson (International Journal of Industrial Engineering and Engineering Management, 2022)
In a heating, ventilation, and air conditioning (HVAC) unit, ducting systems with wind turbines are responses to the system’s high wind energy yields. However, the efficiency of the system is a challenge. To tackle this issue, optimization of process parameters plays a central role. Unfortunately, while applying the Taguchi method as an optimization procedure for high wind energy yields, the existing procedures are not clear enough to project a deep understanding of how to establish priorities among the system's parameters and yet showcase relationships among them. Consequently, this study proposes a new approach, the Taguchi-Pareto DEMATEL (Decision making trial and evaluation laboratory), to establish priorities among the process parameters and concurrently define associations among the parameters of the wind turbine inducting system. The proposed method amalgamates the Taguchi-Pareto method, which prioritizes the process parameters and minimizes the anticipated value of the variance with DEMATEL. The DEMATEL method is infused into the structure to verify interconnection among the wind turbine process parameters and establish a map to show the comparative association within the parameters. Thus, the DEMATEL framework probes and solves the complex energy yield problem of the wind turbine. The parameters used are input air pressure, ducting height, the distance between the blower and the pipe, total effective length, and the gap between the truck and runout. The desired optimal value of parameters for the proposed method are as follows: P2H2TG2EL1BD1, which is interpreted as 2.5m/s of air pressure, 0.5in of height, 1in of truck gap, 0.5in of effective length, and 0.5in of blower distance. The optimized parameters of a ducted wind turbine in an HVAC system could be of vast interest to HVAC systems to plan and monitor wind turbine performance.